2011
DOI: 10.1126/scitranslmed.3001244
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Treatment Expectation on Drug Efficacy: Imaging the Analgesic Benefit of the Opioid Remifentanil

Abstract: Evidence from behavioral and self-reported data suggests that the patients' beliefs and expectations can shape both therapeutic and adverse effects of any given drug. We investigated how divergent expectancies alter the analgesic efficacy of a potent opioid in healthy volunteers by using brain imaging. The effect of a fixed concentration of the μ-opioid agonist remifentanil on constant heat pain was assessed under three experimental conditions using a within-subject design: with no expectation of analgesia, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
527
0
32

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 696 publications
(577 citation statements)
references
References 45 publications
18
527
0
32
Order By: Relevance
“…In clinical settings, placebo responses can confound assumptions about the physical or "true" effects of the treatment, but can also be used to optimize a treatment (44)(45)(46). Although the amount of expectancy, desirability (47), personality traits (48), and biomarkers, like gray matter density of the NAc (25), sometimes correlate with placebo responses, it has been notoriously difficult to predict placebo responses across different contexts (49,50).…”
Section: Common Emotion Appraisal Circuitry Mediated Behavioral and Boldmentioning
confidence: 99%
“…In clinical settings, placebo responses can confound assumptions about the physical or "true" effects of the treatment, but can also be used to optimize a treatment (44)(45)(46). Although the amount of expectancy, desirability (47), personality traits (48), and biomarkers, like gray matter density of the NAc (25), sometimes correlate with placebo responses, it has been notoriously difficult to predict placebo responses across different contexts (49,50).…”
Section: Common Emotion Appraisal Circuitry Mediated Behavioral and Boldmentioning
confidence: 99%
“…Previous studies have shown that nocebo hyperalgesic manipulations heighten HPA activity (Benedetti et al 2006, Johansen et al 2003, cortical activity in pain-related regions (Kong et al 2008;Bingel et al 2011;Schmid et al 2015), pain-related activity in the spinal 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 cord (Geuter & Buchel 2013), blood pressure and reported negative emotions combined with increased pain reports. The findings from the present study further add that successful induction of nocebo expectations increase negative emotions significantly enough to engage physiological and motivational defense systems (Grillon et al 1991), that enhance cortical alertness measured by startle responses.…”
Section: Discussionmentioning
confidence: 99%
“…Cortical areas that are known to be involved in the processing of negative emotions, such as the amygdala (Schmid et al 2015) and the hippocampus (Kong et al 2008;Bingel et al 2011) were shown to be affected by nocebo manipulations. However, only one prior study has directly tested the assumption that nocebo hyperalgesic suggestions increase negative emotions that, in turn, predict increases in pain .…”
Section: Introductionmentioning
confidence: 99%
“…Though not a single volt of current was used, more than two-thirds of the students reported headaches. Bingel et al (2011) pointed out that an individual's expectation of a drug's effect critically influences its therapeutic efficacy. They exposed healthy volunteers to experimental pain stimuli and gave them an active pain-reducing medication and told them that the medication would intensify their pain once the infusion of medication would cease.…”
Section: Psychological Mechanismsmentioning
confidence: 99%